Prevalence of Gastrointestinal Nematodes in Buffalo Calves in Indore and Shajapur districts - Madhya Pradesh - Malviya, Pratibha; Singh, Nidhi; Mehta, H.K; Bagherwal, R.K.; Choudhary, Kamlesh; Agrawal , Vivek (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study was undertaken to record the prevalence of gastro-intestinal nematodes in buffalo calves randomly selected from the dairy farms of two districts viz. Indore and Shajapur of Madhya Pradesh. The results indicate that 60.93% and 61.2% calves were positive for nematode infestation in Indore and Shajapur district of Madhya Pradesh, respectively. Buffalo calves between 0-4 months of age exhibited highest prevalence as compared to the age group of 4-8 months in both districts. Overall prevalence of nematodes infection in male buffalo calves was recorded highest as compared to female ones in Indore and Shajapur districts as 63.53% and 62.22%, respectively. Overall prevalence of nematodes infection in female buffalo calves was recorded in Indore and Shajapur district as 56.14% and 60.26%, respectively.